Risk factors for femoral overgrowth after femoral shortening osteotomy in children with developmental dysplasia of the hip - Pang, Haotian; Guo, Ruoyi; Zhuang, Hanjie; Ben, Yulong; Lou, Yue; Zheng, Pengfei (Frontiers in Pediatrics, 2023)
Objective Developmental dysplasia of the hip (DDH) refers to a series of deformity of acetabulum and proximal femur and abnormal relationship between them, it represents the most common hip disease in children. Overgrowth and limb length discrepancy (LLD) was common complication in children undergoing femoral shortening osteotomy. Therefore, the purpose of this study was to explore the risk factors of overgrowth after femoral shortening osteotomy in children with DDH. Methods We included 52 children with unilateral DDH who underwent pelvic osteotomy combined with femoral shortening osteotomy between January 2016 and April 2018, including seven males (six left and one right hip) and 45 females (33 left and 12 right hips) with an average age of 5.00 ± 2.48 years, and an average follow-up time of 45.85 ± 6.22 months. The amount of overgrowth and limb length discrepancies (LLDs) were calculated. The risk factors of femoral overgrowth ≥1 cm and LLD ≥ 1 cm were analyzed. Results There were statistical differences in age (p < 0.001) and operation duration (p = 0.010) between the two groups with femoral overgrowth <1 cm and ≥1 cm. There was a statistical difference in operation duration (p < 0.001) between the two groups. Age (p < 0.001) was an independent influencing factor of femoral overgrowth in children with unilateral DDH after pelvic osteotomy and femoral shortening osteotomy, and a risk factor (p = 0.008) of LLD in these children. Conclusion The overgrowth and LLD of children with developmental dislocation of hip after pelvic osteotomy and femoral shortening osteotomy are significantly related to age. There was no significant difference between different pelvic osteotomies for femoral overgrowth in children. Therefore, surgeons should consider the possibility of LLD after femoral shortening osteotomy in children of a young age.